The association of cesarean section with overweight and neurodevelopment of Chinese children aged 1–5 months - Zheng, Xiaoguo; Li, Ruili; Wang, Lihong; Yang, Huimin; Li, Linlin; Cui, Jiayin; Zhao, Wenhua; Yang, Zhenyu; Zhang, Qian; Xu, Tao; Wang, Yuying; Chen, Bowen (Frontiers in Pediatrics, 2022)
Objective: The aim of this study was to explore the association of delivery mode with overweight and neurodevelopment of Chinese infants aged 1-5 months. Methods: This study was based on a cross-sectional survey. The data were extracted from the National Nutrition and Health Systematic Survey for children in China which was conducted from 2019 to 2020. Characteristics of parents and children and the delivery mode were obtained using interview-administered questionnaires. Based on WHO child growth standards, body mass index- for age z-score (BMI z) were derived. Children’s neuropsychological development was assessed by a trained child health care physician using the Child Psychological Development Scale. A multivariable logistic regression model was run to analyze the association between delivery mode and infant overweight. A multivariable linear regression model was used to analyze the association between delivery mode and neurodevelopment. Results: A total of 1,347 children aged 1–5 months were included in the present analysis, 35.61% were born via cesarean section, of whom 15.21% were overweight. After adjustment for infant characteristics and parental factors, the multivariable logistic regression model showed cesarean section was significantly associated with the likehood of being overweight (OR =1.95; 95% confidence interval [CI]: 1.27 to 2.98). Children born via cesarean section had a 3.41-point decrease in gross motor development (β =-3.41; 95% CI: -5.77 to -1.05), a 3.65-point decrease in fine motor development (β =-3.65; 95% CI: -6.03 to -1.28), and a 2.96-point in language development (β =-2.96; 95% CI: -5.20 to -0.73), a 1.65-point in total development (β= -1.65; 95% CI: -3.17 to -0.14) compared with those who were vaginal birth. Conclusions: In our study population, cesarean section was associated with overweight and neurodevelopment outcomes. The cesarean section might increase the likehood of infant overweight, and might decrease the developmental scores of gross motor, fine motor and language. Further investigation is needed to replicate these findings in other populations.